YouTube Hindi Videos Proved to be a Valid and Reliable Source of Health Information: A Case Study of COVID-19 Vaccine - Nibha Sinha; Sonali Patle (Indian Journal of Community Medicine)
Background: When the coronavirus vaccine was launched, many Hindi language videos on YouTube were uploaded and audiences were accessing these videos in good numbers. However, the scientific evaluation of these videos was never done. There is a need to understand the accuracy, validity, and quality of these videos so that they can further be utilized for other health awareness purposes. The study objective was to evaluate the validity, quality, and accuracy of the Hindi videos that were viewed the most on YouTube. Material and Methods: Two search terms, “COVID-19 Vaccine–Hindi” and “Corona vaccine Hindi,” were used, and the most viewed 50 videos were selected. All the videos were manually coded and statistically evaluated. Two public health researchers evaluated all the videos blinded to each other using the DISCERN, GQS, and JAMA scales. The correlation score was calculated to know the agreement between them. Scores of professionals and news-based organizations were also compared. Results: Out of all 50 videos, professionals uploaded 48% of videos, and news-based organizations uploaded 46% of videos. The DISCERN median was found to be 9.00 (5–10), the JAMA median score was 6.00 (3–8), and the DISCERN score was 40.50 (16–49). DISCERN, JAMA, and GQS scores were also calculated separately for both observers, and no statistically significant difference was found. Between both the observer’s agreement was found with statistical significance. Conclusion: YouTube was found to be an excellent source of information on the coronavirus vaccine in the Hindi language. Almost all 50 videos had wide viewership, so health professionals and news media organizations cannot ignore this popular platform to improve the health awareness of citizens in a developing country like India.